Motyw rozpoznania a sposób prezentacji postaci kobiecych w palliacie - Maciejewska, Aleksandra (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The article shows how the recognition infuences on the way that female characters are presented in palliata. This motif is very common in Plautus’ and Terence’s comedies. It can be said that anagnorismos enables the introduction of women on the stage and is not at variance with antique customs and decorum.
The recognition motif and the presentation of female characters in Roman comedy
Keywords: antique theatre; lalliata; Plautus; Terence; recognition; women on the stage